A comparative study of different induction techniques (Propofol-Placebo, Propofol-Ephedrine and Propofol- Placebo-Crystalloid) on intubating conditions after rocuronium administration - Muhd Helmi Azmi; Karis Misiran (Penerbit UKM, 2007)
This was a prospective randomized double blind controlled study to compare intubating conditions at 60 seconds with rocuronium 0.6 mg/kg by using three different induction techniques: propofol-placebo (PP), propofol-ephedrine (PE) and propofol-placebocrystalloid (PC). Ninety patients were included and randomly allocated to receive one of the three combinations. The patients were induced using fentanyl 2 μg/kg, followed by propofol 2.5 mg/kg with normal saline as placebo (Group PP and Group PC) or ephedrine 70 μg/kg (Group PE) given over 30 seconds. Subsequently, rocuronium 0.6 mg/kg was given over five seconds and endotracheal intubations were performed 60 seconds later. Intubating conditions were clinically acceptable in all patients except in four patients in PP group, who had poor intubating conditions. The proportion of excellent intubating conditions was significantly highest in Group PE (94%) followed by Group PC (81%) and lowest in Group PP (50%). In conclusion, induction with propofol-ephedrine and propofol-placebo-crystalloid combinations provided significantly better intubating conditions than propofol alone, when rocuronium 0.6 mg/kg was used for intubation at 60 seconds